Insulin resistance and β‐cell dysfunction and the relationship with cardio‐metabolic disorders among women with polycystic ovary syndrome. (9th September 2018) - Mu, Liangshan; Zhao, Yue; Lai, Yuchen; Li, Rong; Qiao, Jie
Summary: Objective: To investigate both independent and combined effects of insulin resistance and β‐cell dysfunction on cardio‐metabolic abnormalities in polycystic ovary syndrome (PCOS). Design: A national epidemiologic survey was performed in reproductive aged females in China from October 2007 to September 2011. Methods: A total of 824 PCOS and 2715 non‐PCOS were included. The Rotterdam Criteria were applied for PCOS diagnosis. We used the homeostasis model assessment of insulin resistance (HOMA‐IR) and HOMA of β‐cell function (HOMA‐β) to evaluate insulin resistance and β‐cell dysfunction, respectively. Results: Compared with non‐PCOS, PCOS showed a higher index of HOMA‐IR and HOMA‐β, and a higher prevalence of obesity, central obesity, and dyslipidaemia. High HOMA‐IR was independently related to a high prevalence of obesity, central obesity, dyslipidaemia, and high blood glucose in PCOS. In contrast, a low index of HOMA‐β index was independently correlated with a low prevalence of obesity, and central obesity, but negatively correlated with an elevated prevalence of high blood glucose in PCOS. In addition, proportion of insulin resistance was higher than that of β‐cell dysfunction in PCOS with cardio‐metabolic disorders. β‐cell dysfunction was negatively correlated with the prevalence of central obesity and obesity. Conclusions: Insulin resistance and β‐cell dysfunction independently affected cardio‐metabolic abnormalities in PCOS, while insulin resistance was correlated with a higher prevalence of cardio‐metabolic abnormalities than that of β‐cell dysfunction. Moreover, β‐cell dysfunction and insulin resistance showed divergent correlations with obesity in PCOS.